Violence and Memory in the Multiple Versions of Claudia Rankine’s Citizen - John K. Young (Transatlantica)
As Claudia Rankine’s 2014 collection Citizen shifts from racialized micro-aggression to police and other white violence against African Americans, the text makes artful use of blank space, with a verso page reading simply “November 23, 2012 / In memory of Jordan Russell Davis” (on the left-hand side) and the recto page bearing only the words “February 15, 2014 / The justice system” along the top of the right-hand page. (Davis, a teenager, was killed at a Jacksonville gas station; the white shooter was eventually convicted of murder after an initial mistrial). The second printing added Michael Brown’s murder in Ferguson to the verso page. Subsequent printings have included more names—first Eric Garner then John Crawford, killed by a police officer while carrying a BB gun in an Ohio Walmart—and eventually sixteen more memorials, including Tamir Rice and Freddie Gray, with a fading stream of “In Memory” stretched across the remainder of the page, and with the recto reading, “because white men can’t / police their imagination / black men are dying.”This paper traces the post-publication variants in Citizen as an index of the book’s attempts to remake itself in response to new tragedies, and to portray white violence more broadly than in the “justice system” alone. It explores the multiple iterations of Citizen through Daniel Ferrer’s distinctions between variant and variation, finding Rankine’s work an exemplary case of the ways in which, as Kinohi Nishikawa has recently argued, “race is not an a priori category to be read into literature, but a complex effect of distinct social, cultural, and textual mediations.”